1999
DOI: 10.1021/jp993210a
|View full text |Cite
|
Sign up to set email alerts
|

The Interface between a Protein Crystal and an Aqueous Solution and Its Effects on Nucleation and Crystal Growth

Abstract: In this paper we report calculations of the concentration profile and the Gibbs free energy of the interface between a protein crystal and an aqueous solution. The calculations are based on a simple, realistic expression for the Gibbs free energy of the solution, which reproduces characteristic features of the protein-water phase diagram, such as the presence of a metastable liquid-liquid immiscibility region. An equation is derived which expresses the coefficient for the contribution of concentration gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 70 publications
5
62
1
1
Order By: Relevance
“…6 even in the stable region the proximity of a¯uid±¯uid critical point may have a signi®cant effect on the dynamics owing to the appearance of critical¯uctuations, which may enhance crystal nucleation 63,64 . The nucleus can also be enveloped by a¯uid layerÐthis coating would alter the surface tension and thus the nucleation and growth process 65 . Within the metastable region the Ostwald rule implies that¯uid± uid phase separation would precede the¯uid±crystal transition.…”
Section: The Effect Of Metastable Statesmentioning
confidence: 99%
“…6 even in the stable region the proximity of a¯uid±¯uid critical point may have a signi®cant effect on the dynamics owing to the appearance of critical¯uctuations, which may enhance crystal nucleation 63,64 . The nucleus can also be enveloped by a¯uid layerÐthis coating would alter the surface tension and thus the nucleation and growth process 65 . Within the metastable region the Ostwald rule implies that¯uid± uid phase separation would precede the¯uid±crystal transition.…”
Section: The Effect Of Metastable Statesmentioning
confidence: 99%
“…This means that the nucleation of crystals in TSC is enhanced because of the presence of metastable amorphous dense droplets, consistent with the previous theoretical predictions. [8][9][10][11] One of the implications associated with the mononuclear mechanism is that all dense droplets can grow large enough to develop a crystal. However, a good deal of experimental evidence shows that, although many dense droplets were created initially, only a fraction of them could successfully produce a crystal.…”
Section: Introductionmentioning
confidence: 99%
“…In a computer simulation study, it was found that the presence of a metastable fluid-fluid critical point drastically changes the pathway for the formation of a critical nucleus and the large density fluctuations near the critical point increase the nucleation rate [8]. Haas and Drenth discuss the nucleation mechanisms in the liquid-liquid phase separation zone [9] and attempt a theoretical explanation for enhanced nucleation rates. Liquid-liquid spinodal decomposition followed by nucleation was proposed by Georgalis et al [10].…”
Section: Introductionmentioning
confidence: 99%